Water Soluble Chitosan from Green Mussel (Perna viridis) Shells and Its Use As Fat-Absorber In Cookies - Aef Permadi; Rufnia Ayu Afifah; Dita Ambar Kartika Apriani; Farida Ariyani (Research and Development Center for Marine and Fisheries Product Processing and Biotechnol, 2022)
Green mussel chitin can be converted by H2O2 into water-soluble chitosan (WSC). This can subsequently be utilized for a variety of different purposes, such as a fat binder. This study examines how different H2O2 concentrations (13, 21.5, and 30%) affected the properties of WSC (yield, moisture content, ash content, degree of deacetylation, and solubility in water and acid). Moreover as well as how WSC (8%, 9%, and 10%) affected the hedonic scores, proximate composition, and fat binding capacity of weight-loss cookies. A single factor Completely Randomized Design and single-factor ANOVA were used to analyze the data, followed by Duncan’s additional testing as necessary. The results showed that water-soluble chitosan was impacted by H2O2 concentration in that its yield and ash content decreased, its color changed to a brownish, and its solubility in acid and moisture content all increased. According to De Garmo’s Effectiveness Index Test, 30% H2O2 concentration resulted in the best WSC. The addition of WSC did not affect the hedonic quality, protein, moisture, or carbohydrate contents of the cookies, but it did have an impact on the ash and fat contents. The ability of all cookie samples in all treatments to bind fat in liquified butter and peanut oil validates the use of cookies containing WSC in body weight loss research.